Method for testing interfacial strength of magnesium-aluminum laminated composite board
By calculating the magnesium-aluminum-like composite plate in the aluminum layer in the aluminum-like composite plate, and select the adhesive or shear method according to its value, the interface intensity test is performed. Based on the problem of low accuracy and poor stability of the intensity test results, the interface intensity test with high accuracy and stability is realized.
Patent Information
- Application Number
- CN202411788323.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The results of the existing magnesium-aluminum layered composite board interface bonding strength test methods are low in accuracy and poor in stability, making it difficult to accurately reflect the interface bonding performance of magnesium-aluminum composite boards designed with different layer thicknesses.
Calculate the tensile strength of the aluminum layer according to QAL = (TAL/T) × σ composite board × K. If QAL ≤ 70MPa, the interface strength of the magnesium and aluminum layer is tested by the adhesive method; Dharma test.
A convenient, time-consuming, accurate, and high stability of magnesium-aluminum-shaped composite plate interface intensity test method is provided, which is suitable for magnesium aluminum composite boards with thick design of different layers.
Smart Images

Figure CN119375145A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite plate performance testing, and in particular to a method for testing the interface strength of a magnesium-aluminum layered composite plate. Background Art
[0002] Metal layered composite materials are new materials that are made by using composite technology to achieve a strong metallurgical bond between two or more metals with different physical, chemical and mechanical properties. Each layer of metal still maintains its original characteristics, but its overall physical, chemical and mechanical properties are greatly improved compared to a single metal, so it can meet the requirements for material performance in special environments.
[0003] Magnesium-aluminum laminated plates have the excellent properties of magnesium, such as low density, high specific strength and specific stiffness, and aluminum, such as high strength and corrosion resistance, and are becoming a new research hotspot. Among them, the aluminum layer can significantly improve the formability of magnesium alloys and improve the corrosion resistance of magnesium alloys. Magnesium-aluminum laminated plates have broad application prospects in the fields of petrochemicals, marine engineering, oil and gas transportation, aerospace, mechanical metallurgy, and household appliances.
[0004] The key technical indicators of magnesium-aluminum layered composite plates are mainly concentrated in strength, formability, bending performance and interface strength. At present, there are relevant test methods for strength, formability and bending performance, while the evaluation method of interface strength is very complicated. Different methods cannot accurately reflect the interface bonding performance of magnesium-aluminum composite plates (especially magnesium-aluminum composite plates with different layer thickness designs).
[0005] That is, the currently used method for testing the interface bonding strength of magnesium-aluminum layered composite plates has the problems of low result accuracy and poor result stability.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a method for testing the interface strength of a magnesium-aluminum layered composite plate to solve or improve the above technical problems.
[0008] The present invention can be implemented like this:
[0009] In a first aspect, the present invention provides a method for testing the interface strength of a magnesium-aluminum laminate, which comprises the following steps: Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Alis the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板 is the tensile strength of the magnesium-aluminum laminated composite plate to be tested, k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum laminated composite plate to be tested;
[0010] If Q Al ≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
[0011] In an optional embodiment, the gluing method includes: cutting a sample to be tested containing a bonding interface of a magnesium layer and an aluminum layer along the thickness direction of the magnesium-aluminum layered composite plate to be tested, and pre-treating the sample to be tested; taking a first stainless steel specimen and a second stainless steel specimen respectively, and pre-treating the surfaces of the two stainless steel specimens;
[0012] The pre-treated sample to be tested is placed between the pre-treated first stainless steel test piece and the pre-treated second stainless steel test piece, and the first stainless steel test piece, the sample to be tested and the second stainless steel test piece are sequentially bonded by a bonding agent;
[0013] The non-bonding surfaces of the two stainless steel specimens were fixed by a clamp, and then a tensile test was performed on a universal testing machine. The maximum interface strength obtained by the test was the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0014] In an optional embodiment, the sample to be tested is a disc with a diameter of 10 mm to 16 mm;
[0015] And / or, the first stainless steel test piece and the second stainless steel test piece are both stainless steel cylinders.
[0016] In an alternative embodiment, the diameter of the stainless steel cylinder is larger than the diameter of the disc.
[0017] In an optional embodiment, the pre-treatment of the test sample and the first stainless steel test piece and the second stainless steel test piece independently includes: cleaning, sandblasting, grinding, removing surface impurities, and solution treatment.
[0018] In an optional embodiment, the solution used for solution treatment is a sulfuric acid-sodium dichromate solution with a concentration of 0.4 mol / L to 0.8 mol / L.
[0019] In an optional embodiment, the surface roughness of the test piece, the first stainless steel test piece and the second stainless steel test piece after pre-treatment are independently ≥ 3.2 Ra.
[0020] In an optional embodiment, the main component of the binder is amino tetrafunctional epoxy resin;
[0021] The bonding process includes: first treating at 130°C to 150°C for 1h to 2h, and then treating at 195°C to 205°C for 1.5h to 2.5h.
[0022] In an optional embodiment, the contact pressure between the fixture and the two stainless steel test pieces is 0.03 MPa to 0.1 MPa.
[0023] In an optional embodiment, the contact pressure between the fixture and the two stainless steel test pieces is 0.05 MPa.
[0024] In an optional embodiment, the clamping force of the tensile test is ≤50N, and the test speed is 0.1m / min to 1m / min.
[0025] In an optional embodiment, the test speed is 0.1 m / min to 0.5 m / min.
[0026] In an optional embodiment, the shearing method includes: cutting downward from the upper surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a first notch, and cutting upward from the lower surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a second notch; the projections of the first notch and the second notch on the same horizontal plane do not overlap; the depth of the first notch or the second notch is the thickness of a single aluminum layer or a single magnesium layer in the magnesium-aluminum layered composite plate to be tested;
[0027] The magnesium-aluminum layered composite plate to be tested with the first notch and the second notch is subjected to a tensile test on a universal testing machine, and the maximum interface strength obtained by the test is the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0028] In an optional embodiment, the shortest horizontal distance between the first notch and the second notch is the overlap width, and the overlap width is 1 mm to 3 mm;
[0029] The distance of the first notch along the length direction of the magnesium-aluminum layered composite plate to be tested is 2 mm, and the distance of the first notch along the width direction of the magnesium-aluminum layered composite plate to be tested is 10 mm.
[0030] In an optional embodiment, the clamping force of the tensile test is ≤10N, and the test speed is 0.05m / min to 0.5m / min.
[0031] In an optional embodiment, the test speed is 0.1 m / min to 0.5 m / min.
[0032] The beneficial effects of the present invention include:
[0033] The present invention creatively provides a unified method for testing the interface strength of magnesium-aluminum composite plates with different layer thickness ratios. Specifically, different testing methods are selected based on different conditions. The method is convenient, time-saving, has small fluctuations in test results, high stability and good accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a schematic diagram of the structure after the disc is fixed to two stainless steel columns in Example 1 of the present invention;
[0036] Figure 2 This is a graph showing the interface strength test in Example 1 of the present invention;
[0037] Figure 3 This is a schematic diagram of cutting the notch in Example 2 of the present invention;
[0038] Figure 4 This is a graph showing the interface strength test in Example 2 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0040] The following is a detailed description of the test method for the interface strength of the magnesium-aluminum layered composite plate provided by the present invention.
[0041] The present invention provides a method for testing the interface strength of a magnesium-aluminum laminate, which comprises the following steps: Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Al is the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板is the tensile strength of the magnesium-aluminum laminated composite plate to be tested, k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum laminated composite plate to be tested;
[0042] If Q Al ≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
[0043] In the present invention, the magnesium-aluminum layered composite plate is obtained by metallurgically combining an initial magnesium plate and an initial aluminum plate, and the surfaces of the initial magnesium plate and the initial aluminum plate are both flat.
[0044] The tensile strength of the initial aluminum plate and the initial magnesium plate can be measured by the GB 228-2020 method. In addition, it can also be obtained according to the specific grades of the aluminum plate and the magnesium plate and the known material properties information. Similarly, the tensile strength of the magnesium-aluminum laminated composite plate to be measured can also be directly measured by the GB 228-2020 method.
[0045] The thickness of the aluminum layer in the magnesium-aluminum layered composite plate to be tested can be obtained by observing the magnesium-aluminum layered composite plate to be tested under a scanning electron microscope. The total thickness of the magnesium-aluminum layered composite plate to be tested can be directly measured.
[0046] In the present invention, the above-mentioned gluing method may include: cutting a sample to be tested containing a bonding interface of a magnesium layer and an aluminum layer along the thickness direction of the magnesium-aluminum layered composite plate to be tested, and pre-treating the sample to be tested; taking a first stainless steel test piece and a second stainless steel test piece respectively, and pre-treating the surfaces of the two stainless steel test pieces;
[0047] The pre-treated sample to be tested is placed between the pre-treated first stainless steel test piece and the pre-treated second stainless steel test piece, and the first stainless steel test piece, the sample to be tested and the second stainless steel test piece are sequentially bonded by a bonding agent;
[0048] The non-bonding surfaces of the two stainless steel specimens were fixed by a clamp, and then a tensile test was performed on a universal testing machine. The maximum interface strength obtained by the test was the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0049] In some optional embodiments, the sample to be tested may be a disc having a diameter of 10 mm to 16 mm (eg, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, or 16 mm).
[0050] The first stainless steel test piece and the second stainless steel test piece are both stainless steel cylinders. The diameter of the stainless steel cylinder is larger than the diameter of the disc, for example, the diameter of the stainless steel cylinder can be 20 mm.
[0051] In some optional embodiments, the pre-treatment of the test sample and the first stainless steel test piece and the second stainless steel test piece independently includes: cleaning, sandblasting, grinding, removing surface impurities, and solution treatment.
[0052] The cleaning can be performed with acetone, and the polishing can be performed with sandpaper. The solution used for the solution treatment is a sulfuric acid-sodium dichromate solution with a concentration of 0.4 mol / L to 0.8 mol / L (such as 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L or 0.8 mol / L, etc.).
[0053] The surface roughness of the pre-treated test piece, the first stainless steel test piece and the second stainless steel test piece are independently ≥ 3.2Ra.
[0054] In some optional embodiments, the main component of the binder is amino tetrafunctional epoxy resin.
[0055] Exemplarily, the bonding process may include: first treating at 130°C to 150°C (such as 130°C, 135°C, 140°C, 145°C or 150°C, etc.) for 1h to 2h (such as 1h, 1.5h or 2h, etc.), and then treating at 195°C to 205°C (such as 195°C, 200°C or 250°C, etc.) for 1.5h to 2.5h (such as 1.5h, 2h or 2.5h, etc.). By following the above bonding process, the first stainless steel test piece, the sample to be tested and the second stainless steel test piece can be effectively bonded.
[0056] In some optional embodiments, the contact pressure between the fixture and the two stainless steel test pieces can be 0.03MPa to 0.1MPa, such as 0.03MPa, 0.04MPa, 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa, 0.09MPa or 0.1MPa, etc., or other values within the range of 0.03MPa to 0.1MPa. In some typical embodiments, the contact pressure between the fixture and the two stainless steel test pieces is 0.05MPa.
[0057] In some optional embodiments, the clamping force of the tensile test is ≤50N, such as 50N, 45N, 40N or 35N. The test speed can be 0.1m / min to 1m / min, such as 0.1m / min, 0.2m / min, 0.4m / min, 0.6m / min, 0.8m / min or 1m / min, or other values within the range of 0.1m / min to 1m / min. In some typical embodiments, the test speed is 0.1m / min to 0.5m / min.
[0058] During the above-mentioned adhesive test, the maximum interface strength obtained by the tensile test on the universal testing machine refers to the maximum force required by the universal testing machine when the interface is separated. This maximum force is the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0059] In the present invention, the shearing method may include: cutting downward from the upper surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a first notch, and cutting upward from the lower surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a second notch; the projections of the first notch and the second notch on the same horizontal plane do not overlap; the depth of the first notch or the second notch is the thickness of a single aluminum layer or a single magnesium layer in the magnesium-aluminum layered composite plate to be tested;
[0060] The magnesium-aluminum layered composite plate to be tested with the first notch and the second notch is subjected to a tensile test on a universal testing machine, and the maximum interface strength obtained by the test is the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0061] In some optional embodiments, the first notch and the second notch are both located in the middle area of the magnesium-aluminum layered composite plate to be tested, and the shortest distance between the first notch and the center of the magnesium-aluminum layered composite plate to be tested is equal to the shortest distance between the second notch and the center of the magnesium-aluminum layered composite plate to be tested.
[0062] In some optional embodiments, the shortest horizontal distance between the first notch and the second notch is the overlap width, and the overlap width can be 1 mm to 3 mm, such as 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm, or other values within the range of 1 mm to 3 mm.
[0063] In some optional embodiments, a long strip sample (e.g., 45 mm in length and 10 mm in width) may be cut from the magnesium-aluminum layered composite plate to be tested, the sample containing the bonding interface between the aluminum layer and the magnesium layer, and then a first notch and a second notch may be cut from the sample.
[0064] In some optional embodiments, the distance of the first notch along the length direction of the magnesium-aluminum layered composite plate to be tested may be 2 mm, and the distance of the first notch along the width direction of the magnesium-aluminum layered composite plate to be tested may be 10 mm.
[0065] In some optional embodiments, the clamping force of the tensile test is ≤10N, such as 10N, 8N or 5N. The test speed can be 0.05m / min to 0.5m / min, such as 0.05m / min, 0.1m / min, 0.2m / min, 0.3m / min, 0.4m / min or 0.5m / min, or other values within the range of 0.05m / min to 0.5m / min. In some typical embodiments, the test speed is 0.1m / min to 0.5m / min.
[0066] During the shear test, the maximum interface strength obtained by the tensile test on the universal testing machine refers to the maximum force required by the universal testing machine when the interface separates. The maximum force is the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
[0067] It should be noted that, in the present invention, the principle of performing a tensile test on a universal testing machine can refer to the relevant prior art, and no further elaboration or limitation is made here.
[0068] As mentioned above, the test method provided by the present invention is suitable for testing the interface bonding strength between the magnesium layer and the aluminum layer in magnesium-aluminum composite plates with different layer thickness designs, and the test results are accurate and stable.
[0069] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0070] Example 1
[0071] In this embodiment, a magnesium-aluminum layered composite plate with a known interface strength of 70 MPa is used as the magnesium-aluminum layered composite plate to be tested to verify the feasibility of the method provided by the present invention.
[0072] Specifically, the magnesium-aluminum layered composite plate to be tested is a three-layer magnesium-aluminum composite plate, and the layer structures are an aluminum layer, a magnesium layer and an aluminum layer with a thickness ratio of 1:4:1.
[0073] The interface bonding strength of the magnesium-aluminum layered composite plate is tested by the following method, and the testing method comprises the following steps:
[0074] S1: According to Q Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Al is the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板is the tensile strength of the magnesium-aluminum layered composite plate to be tested, and k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum layered composite plate to be tested.
[0075] If Q Al ≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminated plate to be tested based on Q Al When ≤70MPa, the interface bonding strength of the composite plate is tested by the adhesive method.
[0076] The tensile strength of the magnesium-aluminum layered composite plate to be tested, the initial aluminum plate and the initial magnesium plate were all tested using the GB 228-2020 method, and the results were: the tensile strength of the magnesium-aluminum layered composite plate to be tested was 275 MPa, the tensile strength of the initial aluminum plate was 280 MPa, and the tensile strength of the initial magnesium plate was 260 MPa.
[0077] Therefore, Q Al =(1 / 6)×275×1.07=49.04MPa.
[0078] S2: Based on Q Al When the pressure is less than 70MPa, the bonding method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
[0079] The method of adhesive test is:
[0080] S21: Cut the test sample (14 mm diameter disc) containing the bonding interface of the magnesium layer and the aluminum layer along the thickness direction of the magnesium-aluminum layered composite plate to be tested, the surface of the disc is cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.6 mol / L, so that the surface roughness of the treated disc is 3.2 Ra. Select two stainless steel columns with a diameter of 20 mm, and the surface of each stainless steel column that is used to contact the disc is also cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.6 mol / L, so that the surface roughness of the treated stainless steel column that is used to contact the disc is 4.5 Ra.
[0081] S22: Coat the surface of the disc treated with S21 with an adhesive (the component is glue composed of amino tetrafunctional epoxy resin), place the disc between the surfaces of two stainless steel columns treated with S21, and fix the two stainless steel columns with a clamp. The contact pressure between the clamp and the stainless steel columns is 0.05 MPa. Then treat it at 140°C for 1.5 hours and then at 200°C for 2 hours to bond and fix the disc to the two stainless steel columns.
[0082] S23: Figure 1 As shown in the figure, after the disc is bonded and fixed to two stainless steel columns, the whole is placed on a universal testing machine for tensile testing, with a clamping force of 30N and a test speed of 0.1m / min to 1m / min. After the tensile test, the maximum interface strength is 69.6MPa (as shown in the figure). Figure 2 shown).
[0083] Therefore, the interface bonding strength of the magnesium-aluminum layered composite plate provided in this embodiment is 69.6 MPa.
[0084] This result is consistent with the actual interface strength, indicating that the testing method provided by the present invention is accurate and feasible.
[0085] Example 2
[0086] In this embodiment, a magnesium-aluminum layered composite plate with a known interface strength of 100 MPa is used as the magnesium-aluminum layered composite plate to be tested to verify the feasibility of the method provided by the present invention.
[0087] Specifically, the magnesium-aluminum layered composite plate to be tested is a three-layer magnesium-aluminum composite plate, and the layer structures are an aluminum layer, a magnesium layer and an aluminum layer with a thickness ratio of 2:2:2.
[0088] The interface bonding strength of the magnesium-aluminum layered composite plate is tested by the following method, and the testing method comprises the following steps:
[0089] S1: According to Q Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Al is the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板 is the tensile strength of the magnesium-aluminum layered composite plate to be tested, and k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum layered composite plate to be tested.
[0090] If Q Al≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminated plate to be tested based on Q Al When ≤70MPa, the interface bonding strength of the composite plate is tested by the adhesive method.
[0091] The tensile strength of the magnesium-aluminum layered composite plate to be tested, the initial aluminum plate and the initial magnesium plate were all tested using the GB 228-2020 method, and the results were: the tensile strength of the magnesium-aluminum layered composite plate to be tested was 300 MPa, the tensile strength of the initial aluminum plate was 320 MPa, and the tensile strength of the initial magnesium plate was 280 MPa.
[0092] Therefore, Q Al =(2 / 6)×300×1.14=114MPa.
[0093] S2: Based on Q Al When the pressure is greater than 70 MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
[0094] The shear test method is:
[0095] S21: Cut a long strip sample with a length of 45 mm and a width of 10 mm along the thickness direction of the magnesium-aluminum layered composite plate to be tested (the long strip sample contains the bonding interface between the aluminum layer and the magnesium layer). Figure 3 As shown, a first notch of 2mm×10mm is obtained by cutting downward from the upper surface of the long strip sample; a second notch of 2mm×10mm is obtained by cutting upward from the lower surface of the long strip sample. The depth of the second notch is the depth of a single layer of aluminum, and the depth of the first notch is the total thickness of the long strip sample minus the depth of the first notch. The projections of the first notch and the second notch on the same horizontal plane do not overlap, and the shortest horizontal distance between the first notch and the second notch is the overlap width, which is 2mm.
[0096] S22: The long strip sample with the first notch and the second notch in S21 is placed on a universal testing machine for tensile testing. The clamping force is 10N and the test speed is 0.1m / min to 1m / min. After the tensile test, the maximum interface strength is 100.50MPa (such as Figure 4 shown).
[0097] Therefore, the interface bonding strength of the magnesium-aluminum layered composite plate provided in this embodiment is 100.50 MPa.
[0098] This result is consistent with the actual interface strength, indicating that the testing method provided by the present invention is accurate and feasible.
[0099] Example 3
[0100] In this embodiment, a magnesium-aluminum layered composite plate with a known interface strength of 85 MPa is used as the magnesium-aluminum layered composite plate to be tested to verify the feasibility of the method provided by the present invention.
[0101] Specifically, the magnesium-aluminum layered composite plate to be tested is a two-layer magnesium-aluminum composite plate, and the layer structures are respectively an aluminum layer and a magnesium layer with a thickness ratio of 1:4.
[0102] The interface bonding strength of the magnesium-aluminum layered composite plate is tested by the following method, and the testing method comprises the following steps:
[0103] S1: According to Q Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Al is the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板 is the tensile strength of the magnesium-aluminum layered composite plate to be tested, and k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum layered composite plate to be tested.
[0104] If Q Al ≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminated plate to be tested based on Q Al When ≤70MPa, the interface bonding strength of the composite plate is tested by the adhesive method.
[0105] The tensile strength of the above-mentioned magnesium-aluminum layered composite plate to be tested, the initial aluminum plate and the initial magnesium plate were all tested using the GB 228-2020 method, and the results were: the tensile strength of the magnesium-aluminum layered composite plate to be tested was 260 MPa, the tensile strength of the initial aluminum plate was 280 MPa, and the tensile strength of the initial magnesium plate was 250 MPa.
[0106] Therefore, Q Al =(1 / 5)×260×1.12=58.24MPa.
[0107] S2: Based on Q Al When the pressure is less than 70MPa, the bonding method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
[0108] The method of adhesive test is:
[0109] S21: Cut the test sample (16mm diameter disc) containing the bonding interface of the magnesium layer and the aluminum layer along the thickness direction of the magnesium-aluminum layered composite plate to be tested, the surface of the disc is cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.6mol / L, so that the surface roughness of the treated disc is 3.2Ra. Select two stainless steel columns with a diameter of 20mm, and the surface of each stainless steel column that is used to contact the disc is also cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.4mol / L, so that the surface roughness of the stainless steel column that is used to contact the disc is 3.2Ra.
[0110] S22: Coat the surface of the disc treated with S21 with an adhesive (the component is glue composed of amino tetrafunctional epoxy resin), place the disc between the surfaces of two stainless steel columns treated with S21, and fix the two stainless steel columns with a clamp. The contact pressure between the clamp and the stainless steel columns is 0.1 MPa. Then treat it at 150°C for 1 hour and then at 205°C for 1.5 hours to bond and fix the disc to the two stainless steel columns.
[0111] S23: After the disc is bonded and fixed to the two stainless steel columns, the whole is placed on a universal testing machine for tensile testing, with a clamping force of 30N and a test speed of 0.1m / min to 1m / min. After the tensile test, the maximum interface strength is 84.6MPa.
[0112] Therefore, the interface bonding strength of the magnesium-aluminum layered composite plate provided in this embodiment is 84.6 MPa.
[0113] This result is consistent with the actual interface strength, indicating that the testing method provided by the present invention is accurate and feasible.
[0114] Comparative Example 1
[0115] The materials used in this comparative example are the same as those in Example 1, except that the shear method is adopted for testing.
[0116] The shear test method is:
[0117] Cut a strip sample with a length of 45 mm and a width of 10 mm along the thickness direction of the magnesium-aluminum layered composite plate to be tested (the strip sample contains the bonding interface between the aluminum layer and the magnesium layer). Cut downward from the upper surface of the strip sample to obtain a first notch of 2 mm × 10 mm; cut upward from the lower surface of the strip sample to obtain a second notch of 2 mm × 10 mm. The depth of the first notch is the depth of a single layer of aluminum, and the depth of the second notch is the total thickness of the strip sample minus the depth of the first notch. The projections of the first notch and the second notch on the same horizontal plane do not overlap, and the shortest horizontal distance between the first notch and the second notch is the overlap width, which is 2 mm.
[0118] The long strip sample with the first notch and the second notch is placed on a universal testing machine for tensile testing. The clamping force is 10N and the test speed is 0.1m / min to 1m / min.
[0119] After tensile testing, the aluminum side broke in the test results, the interface was not pulled apart, and the interface strength could not be obtained.
[0120] Comparative Example 2
[0121] The materials used in this comparative example are the same as those in Example 2, except that the adhesive method is used for testing.
[0122] The method of adhesive test is:
[0123] The sample to be tested (a disc with a diameter of 14 mm) containing the bonding interface of the magnesium layer and the aluminum layer is cut along the thickness direction of the magnesium-aluminum layered composite plate to be tested. The surface of the disc is cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.6 mol / L, so that the surface roughness of the treated disc is ≥ 3.2 Ra. Two stainless steel columns with a diameter of 20 mm are selected, and the surface of each stainless steel column that is used to contact the disc is also cleaned with acetone, sandblasted, and polished with sandpaper to remove surface impurities, and then the surface is treated with a sulfuric acid-sodium dichromate solution with a concentration of 0.6 mol / L, so that the surface roughness of the treated stainless steel column that is used to contact the disc is 3.2 Ra.
[0124] An adhesive (containing glue composed of amino tetrafunctional epoxy resin) is coated on the surface of the disc after the above treatment, and the disc is placed between the surfaces of two stainless steel columns after the above treatment. The two stainless steel columns are fixed with a clamp, and the contact pressure between the clamp and the stainless steel column is 0.05 MPa. Then, the disc is treated at 140°C for 1.5 hours and then at 200°C for 2 hours to bond and fix the disc to the two stainless steel columns.
[0125] After the disc is bonded and fixed to two stainless steel columns, the whole is placed on a universal testing machine for tensile testing, with a clamping force of ≤50N and a test speed of 0.1m / min to 1m / min.
[0126] After tensile testing, the interface was not pulled apart and the interface strength could not be obtained.
[0127] In summary, the present invention provides a unified method for testing the interface strength of magnesium-aluminum composite plates with different layer thickness ratios. The testing method is convenient, time-saving, has small fluctuation in test results, high stability and good accuracy.
[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for testing the interface strength of a magnesium-aluminum laminate, characterized in that: The following steps are involved: According to Q Al =(t Al / t 总 )×σ 复合板 ×k to calculate the tensile strength of the aluminum layer in the magnesium-aluminum laminated plate to be tested; where Q Al is the tensile strength of the aluminum layer in the magnesium-aluminum laminate to be tested, t Al is the thickness of the aluminum layer in the magnesium-aluminum laminate to be tested, t 总 is the total thickness of the magnesium-aluminum laminate to be tested, σ 复合板 is the tensile strength of the magnesium-aluminum laminated composite plate to be tested, k is the ratio of the tensile strength of the initial aluminum plate to the initial magnesium plate in the magnesium-aluminum laminated composite plate to be tested; If Q Al ≤70Mpa, the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum laminate to be tested is tested by the adhesive method; if Q Al >70MPa, the shear method is used to test the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate to be tested.
2. The testing method according to claim 1, characterized in that: The gluing method comprises: cutting a sample to be tested containing a bonding interface of a magnesium layer and an aluminum layer along the thickness direction of the magnesium-aluminum layered composite plate to be tested, and pre-treating the sample to be tested; taking a first stainless steel test piece and a second stainless steel test piece respectively, and pre-treating the surfaces of the two stainless steel test pieces; The pre-treated sample to be tested is placed between a pre-treated first stainless steel specimen and a pre-treated second stainless steel specimen, and the first stainless steel specimen, the sample to be tested and the second stainless steel specimen are sequentially bonded by a bonding agent; The non-bonding surfaces of the two stainless steel specimens were fixed by a clamp, and then a tensile test was performed on a universal testing machine. The maximum interface strength obtained by the test was the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
3. The testing method according to claim 2, characterized in that: The sample to be tested is a disc with a diameter of 10 mm to 16 mm; And / or, the first stainless steel test piece and the second stainless steel test piece are both stainless steel cylinders; Preferably, the diameter of the stainless steel cylinder is larger than the diameter of the disc.
4. The testing method according to claim 2, characterized in that: The pre-treatment of the test sample and the first stainless steel test piece and the second stainless steel test piece independently includes: cleaning, sandblasting, grinding, removing surface impurities, and solution treatment; Preferably, the solution used for solution treatment is a sulfuric acid-sodium dichromate solution with a concentration of 0.4 mol / L to 0.8 mol / L; Preferably, the surface roughness of the pre-treated specimen, the first stainless steel specimen and the second stainless steel specimen are independently ≥ 3.2 Ra.
5. The testing method according to claim 2, characterized in that: The main component of the binder is amino tetrafunctional epoxy resin; The bonding process includes: first treating at 130°C to 150°C for 1h to 2h, and then treating at 195°C to 205°C for 1.5h to 2.5h.
6. The testing method according to claim 2, characterized in that: The contact pressure between the fixture and the two stainless steel test pieces is 0.03MPa to 0.1MPa; Preferably, the contact pressure between the fixture and the two stainless steel test pieces is 0.05 MPa.
7. The testing method according to claim 2, characterized in that: The clamping force of the tensile test is ≤50N, and the test speed is 0.1m / min~1m / min; Preferably, the test speed is 0.1 m / min to 0.5 m / min.
8. The testing method according to claim 1, characterized in that: The shearing method includes: cutting downward from the upper surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a first notch, and cutting upward from the lower surface of the magnesium-aluminum layered composite plate to be tested along the thickness direction of the magnesium-aluminum layered composite plate to be tested to obtain a second notch; the projections of the first notch and the second notch on the same horizontal plane do not overlap; the depth of the first notch or the second notch is the thickness of a single aluminum layer or a single magnesium layer in the magnesium-aluminum layered composite plate to be tested; The magnesium-aluminum layered composite plate to be tested having the first notch and the second notch is subjected to a tensile test on a universal testing machine, and the maximum interface strength obtained from the test is the interface strength between the magnesium layer and the aluminum layer in the magnesium-aluminum layered composite plate.
9. The testing method according to claim 8, characterized in that: The shortest horizontal distance between the first notch and the second notch is the overlap width, and the overlap width is 1 mm to 3 mm.
10. The testing method according to claim 9, characterized in that: The clamping force of the tensile test is ≤10N, and the test speed is 0.05m / min~0.5m / min; Preferably, the test speed is 0.1 m / min to 0.5 m / min.
Citation Information
Patent Citations
Method for calculating critical value of roughness of rough bonding interface
CN107421886A
Method for establishing stainless steel bar concrete mesoscopic numerical model
CN110442922A
Process parameter data and method for cooperatively regulating and controlling comprehensive performance of heterogeneous layered composite material
CN118886313A
Adhesion strength evaluation sample preparation method for copper-clad laminate
JP2021019019A
Method of determining adhesion strength of joints
SU1305577A1